Evaluación del efecto de la poda de recepa y cuatro tipos de bioestimulantes en la productividad de café (coffea arabica), en el Cantón Caluma. - Pataron Guailla, Franklin Rolando (2024)
Coffee belongs to the Coffea genus of the Rubiaceae family and has around 103 species, but only two of them have economic importance, Arabica coffee (Coffea arabica L.) and Robusta (Coffea canephora Pierre). The production of Arabica coffee occupies around 70% of the world production, which is around 90 million 60 kg bags. Ecuador is one of the 14 countries in the world that has mixed production, that is to say, both commercial species (Arabica and Robusta) are cultivated. The main objective of this research was to evaluate the effect of pruning and four types of biostimulants on coffee productivity. The specific objectives were: i) To identify in which of the treatments the highest production averages were obtained in the rehabilitated coffee plantations by means of pruning, ii) To determine the relationship between the components of yield and production. For this purpose, the following variables were evaluated Shoot height (AB), Shoot diameter (DB), Incidence of anthracnose (IA), Incidence of rust (IR), Incidence of rooster's eye (IOG), Incidence of leaf miner (IMH), Number of dead plants per treatment (NPMT), Number of flowering plants per treatment (NPFT), Number of branches per plant (NRPP), Number of branches per plant (NRPP) and Number of flowering plants per treatment (NPFT), Number of branches per plant (NRPP), Number of branches with fruit per plant (NRCFP), Number of branches without fruit per plant (NRSFP), Weight of 100 ripe cherries (PCCM), Weight of cherries per plant (PCPP), Weight of 100 seeds (PCS), Weight of seeds per plant (PSP), Weight in cherry coffee (PCC), Weight in parchment coffee (PCP). The experimental materials used were: arabica coffee plants and 4 biostimulants. The type of experimental design used was descriptive and inferential statistics, Fisher's test at 5% and 1%, Tukey's test 5% and correlation and linear regression analysis. It was determined that the greatest response was registered in T1: Phyto hormonal plus 1.5 ml/l, in the variables shoot height with 1.46 m, weight in cherry coffee with 1885.95 kg/ha-1 and also in the component weight in parchment coffee with 422.93 kg/ha. Also for the parchment coffee weight variable, T1: Phyto hormonal plus 1.5 ml/l obtained the best average with 422.93 kg/ha-1, followed by T4: New giberned 10g/ha with 328.95 kg/ha-1 and T3: Cytokin 750cc/ 100 l, with 266.29 kg/ha-1. It was identified that treatments T1: Phyto hormonal plus 1.5 ml/l and T4: New giberned 10g/ha were the most effective treatments for the development of agronomic and productive characteristics, because they are phyto-regulators that help plant development.